2012
DOI: 10.2527/jas.2011-4955
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an extract of plant flavonoids (Bioflavex) on rumen fermentation and performance in heifers fed high-concentrate diets1

Abstract: To study the effects of an extract of plant flavonoids [Bioflavex (FL)] in cattle fed highconcentrate diets, 2 experiments were designed. In the first experiment, the effects of Bioflavex on the development of rumen acidosis was evaluated in 8 Holstein-Friesian crossbreed heifers (451 kg; SEM 14.3 kg of BW) using a crossover design. Each experimental period lasted 22 d; from d 1 to 20, the animals were fed rye grass, on d 21 the animals were fasted, and on d 22, rumen acidosis was induced by applying 5 kg of w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

19
99
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(119 citation statements)
references
References 41 publications
19
99
0
1
Order By: Relevance
“…Our results strongly suggest that flavonoids contribute the most to reducing CH 4 production and it may be particularly useful for a general screening for plants possessing antimethanogenic activity. Otherwise, TF and CT fractions are both associated with a lower CH 4 emission, however, the mechanisms through which they decrease CH 4 appear to differ.This supports previous studies which reported that ruminal CH 4 production may be lower when using diets containing flavonoids (Garcıa-Gonzalez et al, 2008a b; Balcells et al, 2012;Oskoueian et al, 2013 ;Seradj et al, 2014). But this is not always the case (Broudiscou et al, 2000(Broudiscou et al, , 2002.…”
Section: Ruminal Fermentation Parameterssupporting
confidence: 91%
“…Our results strongly suggest that flavonoids contribute the most to reducing CH 4 production and it may be particularly useful for a general screening for plants possessing antimethanogenic activity. Otherwise, TF and CT fractions are both associated with a lower CH 4 emission, however, the mechanisms through which they decrease CH 4 appear to differ.This supports previous studies which reported that ruminal CH 4 production may be lower when using diets containing flavonoids (Garcıa-Gonzalez et al, 2008a b; Balcells et al, 2012;Oskoueian et al, 2013 ;Seradj et al, 2014). But this is not always the case (Broudiscou et al, 2000(Broudiscou et al, , 2002.…”
Section: Ruminal Fermentation Parameterssupporting
confidence: 91%
“…Condensed tannins (a polyflavonoid) can mitigate methane emission by feeding Leucaena leucocephala in sheep [5] . It is effective in improving rumen fermentation and reducing the incidence of rumen acidosis through supplementation of natural flavonoids extract from bitter orange and grapefruit [6] . Sainfoin which contains rich condensed tannins can increase beneficial fatty acids and reduce skatole content in lamb meat [7] .…”
Section: Introductionmentioning
confidence: 99%
“…The plants of interest produce a diverse array of secondary compounds, which have benefits in ruminant production (Wallace, 2004). These compounds, including phenylpropanoids and flavonoids, are known to have an impact on rumen microbial metabolism by inducing changes in the fermentation conditions (pH, propionate proportion, and protein degradation) (Broudiscou et al, 2002;Balcells et al, 2012).…”
Section: Introductionmentioning
confidence: 99%